Relationship between C-reactive protein and physical fitness, physical activity, obesity and selected cardiovascular risk factors in schoolchildren - Hamid Reza Sadeghipour; Ameneh Rahnama; Mohsen Salesi; Nader Rahnama; Hossein Mojtahedi (International Journal of Preventive Medicine, 2010)
Objectives: The aim of this study was to investigate the relation between C-reactive protein (CRP) with physical fitness, physical activity, obesity, and selected cardiovascular risk factors in school -children. Methods: Forty-four boy schoolchildren (mean ± SD: age 10.25 ± 0.75 years, height 144 ± 0.2 cm, body weight 46.1 5± 4.59 kg, body mass index 22.16 ± 2.16 kg/m 2 ) voluntarily participated in this study. Physical fitness and physical activity were assessed using the 20-meter fitness test. Adiposity was estimated using body mass index. Blood samples were taken after an overnight fast and meas-ured for CRP, LDL, HDL and cholesterol. Pearson′s correlation was calculated to determine the relations between these factors. Results: Mean (SD) CRP concentration was 1.07 (0.82) mg/l. A significant correlation was observed between CRP and VO2max (r=-0.45, P= 0.001), body mass index (r=0.55, P=0.000) and cho-lesterol (r=-0.35, P=0.04). No significant relation was found be-tween CRP and physical activity, LDL and HDL (P> 0.05). Moreover, significant associations were observed between body mass index and VO2max (r=-0.33, P=0.02) and physical activity (r=-0.43, P=0.04). Conclusions: Body mass index was the most powerful predictor of serum concentrations of CRP in schoolchildren. It may be an important factor to control body weight to prevent an increase in serum CRP in children and to help the primordial prevention of chronic diseases.